Derivation Requirements on Prime Near-Rings for Commutative Rings - Setyawati, Dian Winda; Habibi, Mochammad Reza; Baihaqi, Komar (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2019)
Near-ring is an extension of ring without having to fulfill a commutative of the addition operations and left distributive of the addition and multiplication operations It has been found that some theorems related to a prime near-rings are commutative rings involving the derivation of the Lie products and the derivation of the Jordan product. The contribution of this paper is developing the previous theorem by inserting derivations to the Lie products and the Jordan product. Keywords: Derivation, Prime Near-Ring, Lie Products and Jordan Products.